Dose-Dependent Increases in Whole-Body Net Protein Balance and Dietary Protein-Derived Amino Acid Incorporation into Myofibrillar Protein During Recovery from Resistance Exercise in Older Men - Andrew M. Holwerda; Kevin J.M. Paulussen; Maarten Overkamp; Joy P. B. Goessens; Irene Krämer; Will K. W. H. Wodzig; Lex B. Verdijk; Luc J. C. van Loon (2019)
Age-related decline in skeletal muscle mass is at least partly attributed to anabolic resistance to food intake. Resistance exercise sensitizes skeletal muscle tissue to the anabolic properties of amino acids.The present study assessed protein digestion and amino acid absorption kinetics, whole-body protein balance, and the myofibrillar protein synthetic response to ingestion of different amounts of protein during recovery from resistance exercise in older men.Forty-eight healthy older men [mean ± SEM age: 66 ± 1 y; body mass index (kg/m2): 25.4 ± 0.3] were randomly assigned to ingest 0, 15, 30, or 45 g milk protein concentrate after a single bout of resistance exercise consisting of 4 sets of 10 repetitions of leg press and leg extension and 2 sets of 10 repetitions of lateral pulldown and chest press performed at 75-80% 1-repetition maximum. Postprandial protein digestion and amino acid absorption kinetics, whole-body protein metabolism, and myofibrillar protein synthesis rates were assessed using primed, continuous infusions of l-[ring-2H5]-phenylalanine, l-[ring-2H2]-tyrosine, and l-[1-13C]-leucine combined with ingestion of intrinsically l-[1-13C]-phenylalanine and l-[1-13C]-leucine labeled protein.Whole-body net protein balance showed a dose-dependent increase after ingestion of 0, 15, 30, or 45 g of protein (0.015 ± 0.002, 0.108 ± 0.004, 0.162 ± 0.008, and 0.215 ± 0.009 μmol Phe · kg-1 · min-1, respectively; P < 0.001). Myofibrillar protein synthesis rates were higher after ingesting 30 (0.0951% ± 0.0062%/h, P = 0.07) or 45 g of protein (0.0970% ± 0.0062%/h, P < 0.05) than after 0 g (0.0746% ± 0.0051%/h). Incorporation of dietary protein-derived amino acids (l-[1-13C]-phenylalanine) into de novo myofibrillar protein showed a dose-dependent increase after ingestion of 15, 30, or 45 g protein (0.0171 ± 0.0017, 0.0296 ± 0.0030, and 0.0397 ± 0.0026 mole percentage excess, respectively; P < 0.05).Dietary protein ingested during recovery from resistance exercise is rapidly digested and absorbed. Whole-body net protein balance and dietary protein-derived amino acid incorporation into myofibrillar protein show dose-dependent increases. Ingestion of ≥30 g protein increases postexercise myofibrillar protein synthesis rates in older men. This trial was registered at Nederlands Trial Register as NTR4492.